Soviet Sociology of International Relations (Czech Journal of International Relations, 1967)
I make some contributions to the perspective of the Soviet sociology of international relations published in the collection of papers and contributions, with which Soviet members spokeat the international sociological congress in March 1966 in Evian. The topic of sociology of international relations was one of the main topics at the congress.V. Semyonov, in his study of Social Class and International Relations, starts from the changes brought about in the concept of both components by the twentieth century and the dark period since the Second World War. It particularly emphasizes the importance of the scientific and technological revolution and the growing role of scientists. Shows, from the social groups acting indirectly in international relations, ie. through the mediation of nations and states, and therefore the prerequisite for illuminating the given question is how and to what extent the interests of individual classes and social groups are promoted within the state.